Discovery and validation of methylation markers for endometrial cancer. Issue 8 (31st March 2014) - Wentzensen, Nicolas; Bakkum‐Gamez, Jamie N.; Killian, J. Keith; Sampson, Joshua; Guido, Richard; Glass, Andrew; Adams, Lisa; Luhn, Patricia; Brinton, Louise A.; Rush, Brenda; d'Ambrosio, Lori; Gunja, Munira; et al.
<x xml:space="preserve">Abstract</x> The prognosis of endometrial cancer is strongly associated with stage at diagnosis, suggesting that early detection may reduce mortality. Women who are diagnosed with endometrial carcinoma often have a lengthy history of vaginal bleeding, which offers an opportunity for early diagnosis and curative treatment. We performed DNA methylation profiling on population‐based endometrial cancers to identify early detection biomarkers and replicated top candidates in two independent studies. We compared DNA methylation values of 1, 500 probes representing 807 genes in 148 population‐based endometrial carcinoma samples and 23 benign endometrial tissues. Markers were replicated in another set of 69 carcinomas and 40 benign tissues profiled on the same platform. Further replication was conducted in The Cancer Genome Atlas and in prospectively collected endometrial brushings from women with and without endometrial carcinomas. We identified 114 CpG sites showing methylation differences with p values of ≤10−7 between endometrial carcinoma and normal endometrium. Eight genes (ADCYAP1, ASCL2, HS3ST2, HTR1B, MME, NPY and SOX1) were selected for further replication. Age‐adjusted odds ratios for endometrial cancer ranged from 3.44 (95%‐CI: 1.33–8.91) for ASCL2 to 18.61 (95%‐CI: 5.50–62.97) for HTR1B. An area under the curve (AUC) of 0.93 was achieved for discriminating carcinoma from benign endometrium. Replication in The Cancer Genome Atlas and in endometrial brushings from an independent study confirmed the candidate markers. This study demonstrates that methylation markers may be used to evaluate women with abnormal vaginal bleeding to distinguish women with endometrial carcinoma from the majority of women without malignancy.